Cultivation of Bacteria From Aplysina aerophoba: Effects of Oxygen and Nutrient Gradients - Gutleben, Johanna; Loureiro, Catarina; Ramírez Romero, Laura Adriana; Shetty, Sudarshan; Wijffels, René H.; Smidt, Hauke; Sipkema, Detmer (Frontiers in Microbiology, 2020)
Sponge-associated bacteria possess biotechnologically interesting properties but as yet have largely evaded cultivation. Thus, ‘omics’-based information on the ecology and functional potential of sponge symbionts is awaiting its integration into the design of innovative cultivation approaches. To cultivate bacteria derived from the marine sponge Aplysina aerophoba, nine novel media formulations were created based on the predicted genomic potential of the prevalent sponge symbiont lineage Poribacteria. In addition, to maintain potential microbial metabolic interactions in vitro, a Liquid-Solid cultivation approach and a Winogradsky-column approach were applied. The vast majority of microorganisms in the inoculum appeared viable after cryopreservation of sponge specimen as determined by selective propidium monoazide DNA modification of membrane-compromised cells, however, only 2% of the initial prokaryotic diversity could be recovered through cultivation. In total, 256 OTUs encompassing seven prokaryotic phyla were cultivated. The diversity of the cultivated community was influenced by the addition of the antibiotic aeroplysinin-1 as well as by medium dilution, rather than carbon source. Furthermore, the Winogradsky-column approach reproducibly enriched distinct communities at different column depths, amongst which were numerous Clostridia and OTUs that could not be assigned to a known phylum. While some bacterial taxa such as Pseudovibrio and Ruegeria were recovered from nearly all applied cultivation conditions, others such as Bacteroidetes were specific to certain medium types. Predominant sponge-associated prokaryotic taxa remained uncultured, nonetheless, alternative cultivation approaches applied here enriched for previously uncultivated microbes.